THE PREHISTORY OF THE SLAVIC CLUSTERS ST IN THE DIACHRONIC CONTEXT - ŠEFČÍK, ONDŘEJ (Slavia Occidentalis, 2020)
The paper aims at presenting four different sources of the Slavic clusters st and analysing them in diachronic contexts, according to their origins (< IE *st, *št, *Ḱt, *Tt). The IE cluster *st has been fully preserved, the late IE cluster *št is de-palatalized as is the satəm-cluster *Ḱt (which has merged with *št in almost all the satəm-languages). The cluster *Tt developed regularly into st in Balto-Slavic and Indo-Iranian languages (and Greek), into 0s in Albanian and u̯t in Armenian – the Armenian development leads to preference for the cluster’s spirantization (as stated earlier by Bartholomae for Indo-Iranian) over the traditional “Brugmannian” affricativization.